Highly adjustable biomaterial networks from three-armed biodegradable macromers. (15th October 2015) - Loth, Rudi; Loth, Tina; Schwabe, Katharina; Bernhardt, Ricardo; Schulz-Siegmund, Michaela; Hacker, Michael C.
Graphical abstract: Abstract: Biocompatible material platforms with adjustable properties and option for chemical modification are warranted for site-specific biomedical applications. To this end, three-armed biodegradable macromers of well-defined chemical characteristics were prepared from trivalent alcohols with different degrees of ethoxylation and different lengths of oligoester domains. A platform of 15 different macromers was established. The macromers were designed to exhibit different hydrophilicities and molecular weights and contained various types of oligoesters such asd, l -lactide, l -lactide and ε-caprolactone. Macromers chemical composition was determined and molecular weights ranged from 900 to 3000 Da. Thermally induced cross-linking of methacrylated macromers was monitored by oscillation rheology. A novel variant of the solid lipid templating technique was established to fabricate macroporous tissue engineering scaffolds from these macromers. Scaffold properties were thoroughly investigated regarding mechanical properties, compositional analysis including methacrylic double bond conversion, microstructure and porosity. Material properties could be controlled by macromer chemistry. By variation of the fabrication procedure and processing parameters scaffold porosity was increased up to 88%. Basic cytocompatibility was assessed including indirect and direct contact methods. The established macromers hold promise for various biomedical purposes. Statement of Significance: Specific biomedical applications require tailored biomaterials with defined properties. We established a macromer platform for preparation of tissue engineering scaffolds with adjustable chemical and mechanical characteristics. Macromers were composed of trivalent core alcohols with different degrees of ethoxylation to which biodegradable domains – lactide or ε-caprolactone – were oligomerized before final methacrylation. The solid lipid templating technique was adapted to fabricate macroporous scaffolds with controlled pore structure and porosity from the developed macromers, which can also be processed by solid freeform fabrication techniques. The material platform relies on clinically established chemistries of the biodegradable domains and the macromer concept enables the fabrication of networks in which cross-polymerization kinetics, mechanical properties and surface hydrophobicity is predefined by macromer chemistry. Cytocompatibility was confirmed by indirect and direct cell contact experiments.